Examining the Impact of Team Identification and Gender on Rival Perceptions and Consumption Intentions of Intercollegiate Athletics Fans - Cody T. Havard; Terry W. Eddy; Timothy D. Ryan (Journal of Applied Sports Management, 2016)
The current study investigated rival perceptions using the Sport Rivalry Fan Perception Scale (SRFPS) (Havard, Gray, Gould, Sharp, & Schaffer, 2013) on a group of male and female intercollegiate athletics fans at various levels of favorite team identification. To this point, the SRFPS has primarily been used to examine highly identified male fans (Havard, Reams, & Gray, 2013; Havard, Wann, & Ryan, 2013). The current study extended previous research on rivalry by finding that rival perceptions were impacted by level of team identification. Specifically, highly identified fans experienced more sense of satisfaction when their favorite team defeated the rival team in direct competition. Additionally, highly identified fans were more likely to attend a rivalry game, watch a rivalry game on television or the Internet, and read about the favorite team when playing a rival team than lowly identified fans. Further, female fans were more likely to watch a rivalry game on television than male fans, and the interaction of team identification and gender indicated that playing a rival team impacts female intentions to attend the game more so than male intentions. Significance of findings, along with implications for practitioners and avenues for future study are presented.
Keywords: rivalry; fan sport rivalry; sport rivalry; fan behavior; intercollegiate athletics; team identification; gender